Makine eğitiminde toplam kalite uygulaması - Yalçın, Fatih (My University, 1999)
In this study, Total Quality Management is applied to the Department of Mechanics, Technical Vocational School that is a two-year school with technician graduates. Failure Mode and Effects Analysis (FMEA) which has an important role as a failure preventive method is applied to the both Lathe Workshop and Dynamics Course at the same school. So, at the first time a model is developed in the field of education by using FMEA. In the first chapter, concept and history of quality are explained, and quality control conception is summarized. Second chapter is concerning with Total Quality Management and its fundamentals, and basic statistical techniques as quality improvement tools. Total Quality Management in education is investigated in the third chapter. Adaptation of the fundamentals of Total Quality Management to education and the studies related to the importance of the roles and performances of the school administrations and instructors in order to improve the quality of both teaching and learning are explained. In addition, some examples on application of Total Quality Management to education in Turkey and abroad are given. In the fourth chapter, definition, objectives, benefits and application phases of FMEA are explained in detail. FMEA is adapted to education and this form is being applied to the Department of Mechanics, Technical Vocational School, Marmara University. Conclusions and remarks are discussed and some proposals are made for future studies in the fifth chapter.
Keywords: EĞİTİM; MAKİNE MÜHENDİSLİĞİ; TOPLAM KALİTE